Preparing for an Australian Football League Women's League Season - Thornton, Heidi Rose; Armstrong, Cameron R.; Rigby, Alex; Minahan, Clare L.; Johnston, Rich D.; Duthie, Grant Malcolm (Frontiers in Sports and Active Living, 2020)
The aims were to investigate the externally measured weekly loads, and the distribution intensity relative to the one-minute maximal mean (MM) intensity of matches. Athletes (n = 28) wore 10 Hz GNSS devices during training and matches. Using raw GNSS files, one-minute moving averages were calculated for speed (m·min-1), and acceleration (m·s-2), and were multiplied by time, specifying total distance, and also by body mass to quantify impulse. The distribution of intensity relative to MMs was calculated, with percentages ranging from zero to 110%, separated into 10% thresholds. Drills were categorized as either; warm-ups, skill drills, games (i.e. small sided games) or conditioning, and also included matches. Linear mixed models determined if the distribution of intensity within each threshold (>50%) varied between drill types and matches, and if the distribution within drill types varied across the season. Effects were described using standardized effect sizes (ES) and 90% confidence limits (CL). Compared to matches, a higher proportion of distance was accumulated at 50% of the MM within warm-ups and conditioning (ES range 0.86 to 1.14). During matches a higher proportion of distance was accumulated at 60% of MM when compared to warms ups, skill drills and conditioning (0.73 to 1.87). Similarly, greater proportion of distance was accumulated between 70-100% MM in matches compared to each drill type (except conditioning) (1.05 to 3.93). Matches had a higher proportion of impulse between 60 to 80% of the MM compared to conditioning drills (0.91 to 3.23). During competition, there was a higher proportion of distance accumulated at 50% MM than general preparation (1.08; ± 0.45). Together, these findings demonstrate the field-based training requirements of an AFLW season. The intensity distribution analysis demonstrated that a higher proportion of distance was covered at higher intensities within matches compared to drills; and the proportion of impulse was higher between 60-80% MM within matches compared to conditioning. Practitioners can therefore ensure athletes are not only exposed to the intensities common within competition, but also the volume accumulated is comparable, which may have positive performance outcomes but is also extremely important in the return to play process.